Awareness and Perspectives on Organ Donation Among College Students: A Descriptive Analysis - Anu Joseph; Praveena Prakash M.; Ann Maria Sebastian; Asna Hashim V.; Aylin Susan Babu; Chris Maria Sony; Christeena Mathews; Georgekutty Gigo; Jaisy James (International Journal of Emergency and Trauma Nursing and Practices, 2024)
This research was carried out to evaluate the understanding and perspectives on organ donation among college students at a designated college in Kottayam. The aims of the research included evaluating the students' knowledge about organ donation, examining their attitudes toward organ donation, creating an informational pamphlet on organ donation, exploring the relationship between knowledge levels and certain demographic variables, and investigating the connection between attitudes and demographic factors. A convenience sampling approach was utilized to recruit 225 participants from the pool of college students in Kottayam. Data was gathered using a specifically developed structured questionnaire to measure knowledge and a 5-point Likert scale to evaluate attitudes toward organ donation. The result showed that majority of the subjects, 135(60%), had average knowledge, 79 (35.1%) had good knowledge, and only 11 (4.9%) had poor knowledge toward organ donation. The majority of subjects, 83 (36.9%), had unfavorable attitude toward organ donation, 69 (30.7%) had neutral attitude, and 73 (32.4%) had favorable attitude toward organ donation. The research outcomes indicated a notable correlation between both knowledge and attitude regarding organ donation and various demographic factors. From this study, it is indicated that majority of the subjects had average knowledge and unfavorable attitude toward organ donation.
Keywords: Knowledge; Organ donation; attitude; college students; demographic factors; structured questionnaire